Effect of nanostructures orientation on electroosmotic flow in a microfluidic channel. (1st June 2017) - Lim, An Eng; Lim, Chun Yee; Lam, Yee Cheong; Taboryski, Rafael; Wang, Shu Rui
Abstract: Electroosmotic flow (EOF) is an electric-field-induced fluid flow that has numerous micro-/nanofluidic applications, ranging from pumping to chemical and biomedical analyses. Nanoscale networks/structures are often integrated in microchannels for a broad range of applications, such as electrophoretic separation of biomolecules, high reaction efficiency catalytic microreactors, and enhancement of heat transfer and sensing. Their introduction has been known to reduce EOF. Hitherto, a proper study on the effect of nanostructures orientation on EOF in a microfluidic channel is yet to be carried out. In this investigation, we present a novel fabrication method for nanostructure designs that possess maximum orientation difference, i.e. parallel versus perpendicular indented nanolines, to examine the effect of nanostructures orientation on EOF. It consists of four phases: fabrication of silicon master, creation of mold insert via electroplating, injection molding with cyclic olefin copolymer, and thermal bonding and integration of practical inlet/outlet ports. The effect of nanostructures orientation on EOF was studied experimentally by current monitoring method. The experimental results show that nanolines which are perpendicular to the microchannel reduce the EOF velocity significantly (approximately 20%). This flow velocity reduction is due to the distortion of local electric field by the perpendicular nanolines at the nanostructured surface as demonstrated by finite element simulation. In contrast, nanolines which are parallel to the microchannel have no effect on EOF, as it can be deduced that the parallel nanolines do not distort the local electric field. The outcomes of this investigation contribute to the precise control of EOF in lab-on-chip devices, and fundamental understanding of EOF in devices which utilize nanostructured surfaces for chemical and biological analyses.